El impuesto territorial en Chile ¿descentraliza y desconcentra? - Daher, Antonio (Revista EURE - Revista de Estudios Urbano Regionales, 1995)
Structural changes in the Chilean economy over the past years and its very heterogenous territorial impact are expressed in the State re-appraisal of 1990 that, updated in 1993, can verify that 56% of the national under appraisal is located in the Metropolitan Region, and one third of the countryÍ€™s total under-appraisal is found in the East part of Santiago, thus making evident a quite unequal social and tax situation. The central thesis of article in which both the decentralizing effect of territorial tax -due do its contribution to municipal financing-, as well as its disconcerting effect -since it is redistributed among communities of diffening incomes and regions- are weakened by the existence of numerous implicit subsidies and tacit socio-territorial transfers associated to a tax base that is inert when met by the dissimilar economic dynamisms of the regions. Í 